OPTIMIZATION OF C.45 ALGORITHM WITH SPLITTING METHOD FOR TODDLER NUTRITION CLASSIFICATION - Prayoga, I Made Ari; Fredlina, Ketut Queena; Utami, Nengah Widya (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
Toddler nutritional health is a critical aspect of community development, yet Indonesia continues to face significant challenges in this domain. Posyandu Manukaya Village, a village-level community health service unit, struggles with identifying toddler nutritional status due to manual record-keeping. This study addresses the issue by applying the C4.5 algorithm to classify toddler nutritional status using data from the Tampaksiring I Health Center, comprising a clean dataset of 970 entries. The research adopts the CRISP-DM (Cross Industry Standard Process for Data Mining) framework, with tailored stages including data preparation, model training, and evaluation using confusion matrix. The study identified weight (BB) as the most influential attribute for classification. Among the three attribute separation methods tested, Gain Ratio achieved the best accuracy of 89%, followed by Information Gain at 88%, and Gini Index at 86%. The resulting model was integrated into a simple website using Flask and Joblib, enabling early detection of toddler nutritional status. This research demonstrates the potential of integrating machine learning into public health initiatives and provides a strong foundation for enhancing toddler health monitoring at Posyandu Manukaya Village. Future research should use larger, balanced datasets and more attributes to enhance the model and support early toddler health interventions.